ANALISIS KESULITAN BELAJAR DI MASA PEMBELAJARAN JARAK JAUH (PJJ) SD NEGERI 104310 TEGAL SARI T.A 2021 / 2022 - Siska Andila (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2023)
This research is entitled "Analysis of Learning Difficulties in the Distance Learning Period (PJJ) SD NEGERI 104310 Tegal Sari T.A 2021 / 2022". The background of this research is the outbreak of the Covid-19 virus which requires schools in Indonesia to conduct distance learning (PJJ), including at SD Negeri 104310. So that researchers will analyze how and what learning difficulties were found. during the implementation of distance learning (PJJ). This problem makes researchers interested in conducting further research. The purpose of this study was to find out how the learning difficulties in SD Negeri 104310 Tegal Sari are and what factors influence these learning difficulties. This type of research is a qualitative research. The data obtained from this study using observation, interviews with teachers, students, and parents of students as well as documentation. The results of this study reveal how learning difficulties are found during the implementation of distance learning. And find out what factors influence the learning difficulties. The results of this study found that there were internal and external factors that caused students to have learning difficulties during the distance learning period. Internal factors are factors that come from within the perpetrators of teaching and learning activities such as from teachers and students, while external factors are factors that come from the learning environment, such as the school environment, family environment and community environment.